Exercise training and metformin, but not exercise training alone, decreases insulin production and increases insulin clearance in adults with prediabetes - Viskochil, Richard; Malin, Steven K.; Blankenship, Jennifer M.; Braun, Barry (Journal of applied physiology (1985), 2017)
Adding metformin to exercise does not augment the effect of training alone to boost whole body insulin sensitivity and lower circulating insulin concentrations. Although lower insulin concentrations (lower supply) following lifestyle and/or pharmacological interventions are primarily attributed to reductions in insulin secretion that match increases in peripheral insulin sensitivity (lower demand), it is unclear whether exercise and/or metformin exert direct effects on insulin production, extraction, or clearance. Thirty-six middle-aged, obese, sedentary adults with prediabetes were randomized to placebo (P), metformin (M), exercise and placebo (E+P), or exercise and metformin (E+M) for 12 wk. Fasting plasma proinsulin (an indicator of insulin production), C-peptide, insulin, and glucose were collected before and after the intervention. Peripheral insulin sensitivity (euglycemic clamp), hepatic insulin extraction, insulin clearance, body weight, and cardiorespiratory fitness were also measured. Fasting proinsulin was unchanged following P (19.4 ± 10.1 vs. 22.6 ± 15.0 pmol/l), E+P (15.1 ± 7.4 vs. 15.5 ± 7.4 pmol/l), or M (24.8 ± 18.9 vs. 16.7 ± 20.3 pmol/l) but was significantly reduced after E+M (18.6 ± 11.9 vs. 13.9 ± 6.7 pmol/l; P = 0.04). Insulin clearance was significantly greater following M (384.6 ± 19.4 vs. 477.4 ± 49.9; P = 0.03) and E+M (400.1 ± 32.0 vs. 482.9 ± 33.9; P = 0.02) but was unchanged in P or E+P. In this study, metformin combined with exercise training reduced circulating proinsulin, and both groups taking metformin increased insulin clearance. This suggests that adding metformin to exercise may augment or attenuate training effects depending on the outcome or organ system being assessed. NEW & NOTEWORTHY Exercise is increasingly viewed as medication, creating a need to understand its interactions with other common medications. Research suggests metformin, a widely prescribed diabetes medication, may diminish the benefits of exercise when used in combination. In this study, however, metformin combined with exercise training, but not exercise alone, lowered proinsulin concentrations and increased insulin clearance in adults with prediabetes. This may directly influence personalized prescriptions of lifestyle and/or pharmacology to reduce diabetes risk.